"Did You Think You Would Die?": Fear of Death and Its Relationship to the Development of Posttraumatic Stress Disorder After Traumatic Injury. Issue 2 (15th January 2022) - Simske, Natasha M.; Joseph, Noah M.; Rascoe, Alexander; Kalina, Mark; Simpson, Megen; Hendrickson, Sarah B.; Vallier, Heather A.
Abstract : Introduction: Patient-specific factors may influence posttraumatic stress disorder (PTSD) development and warrant further examination. This study investigates potential association between patient-reported fear of death at the time of injury and development of PTSD. Methods: Over 35 months, 250 patients were screened for PTSD at their first posthospitalization clinic visit and were asked "Did you think you were going to die from this injury?" (yes or no). PTSD screening was conducted using the PTSD checklist for DSM-5 questionnaire. A score ≥33 was considered positive for PTSD, and patients were offered ancillary psychiatric services. Retrospectively, medical records were reviewed for baseline demographics and injury information. Results: Forty-three patients (17%) indicated a fear of death. The mean age was 46 years, with patients who feared death being younger (36 versus 48, P < 0.001), and 62% were male. The most common mechanisms of injury were motor vehicle or motorcycle collisions (30%) and ground-level falls (21%). Gunshot wounds were more common among patients who feared death from trauma (44% versus 7%, P < 0.001). PTSD questionnaires were completed a median of 26 days after injury, with an average score of 12.6. PTSD scores were higher for patients with fear of death (32.7 versus 8.5), and these patients required more acute interventions (47% versus 7%), both P < 0.001. After multivariable logistic regression, patients who thought that they would die from their trauma had >13 times higher odds of developing PTSD (odds ratios: 13.42, P < 0.0001). Apart from positive psychiatric history (OR: 5.46, P = 0.001), no factors (ie, age, sex, mechanism, or any injury or treatment characteristic) were predictive of positive PTSD scores on regression. Dicussion: Patients who reported fear of death at the time of injury were 13 times more likely to develop PTSD. Simply asking patients whether they thought that they would die at the time of injury may prospectively identify PTSD risk. Level of Evidence: Prognostic Level II